Forest Diversity of Nepal's Protected areas in the Mountains - Shrestha, Tirtha Bahadur (Himalayan Review, 2009)
Key words: Terrestrial ecosystem, Protected area, Phytogeographic provinces, Bio-diversity The Himalayan Review 35-36 (2004-2005) 25-28